Associations of mortality relative risk, smoking status, alcohol intake, and educational level in women - V. V. Konstantinov; S. A. Shalnova; C. V. Kireev; T. N. Timofeeva; D. B. Shestov; A. V. Kapustina; Yu. A. Balanova; I. N. Lel’chuk; A. D. Deev (Кардиоваскулярная терапия и профилактика, 2007)
The authors assess relative risk (RR) of coronary heart disease (CHD), stroke (S), cardiovascular disease (CVD), and total mortality, according to smoking status, alcohol intake, and educational level in women. In ex-smokers and current smokers, mortality RR was significantly and dose-dependently increased. In occasional and low-dose drinkers, RR of CVD, CHD, and total mortality was reduced. At the same time, in moderate drinkers, RR was similar to that in frequent and high-dose drinkers. Mortality RR was inversely linked to educational level: in highly educated women, RR was substantially lower than in participants with lower educational levels. The authors assess relative risk (RR) of coronary heart disease (CHD), stroke (S), cardiovascular disease (CVD), and total mortality, according to smoking status, alcohol intake, and educational level in women. In ex-smokers and current smokers, mortality RR was significantly and dose-dependently increased. In occasional and low-dose drinkers, RR of CVD, CHD, and total mortality was reduced. At the same time, in moderate drinkers, RR was similar to that in frequent and high-dose drinkers. Mortality RR was inversely linked to educational level: in highly educated women, RR was substantially lower than in participants with lower educational levels.